SEGREGATION STUDY IN SOLID INTERGRANULAR - Tapia Huanambal, N. (1998)
The investigation of the phenomenon of intergranular segregation in solids is a very important area of ​​materials science. This phenomenon plays an active role in modifying the various properties that have materials, which are very important for many industries (the adhesion of thin films in the electronics industry, fatigue and stress corrosion of metals, etc. .). We present a statistical thermodynamic treatment of the phenomenon of intergranular segregation consisting of one and two component systems.